An analysis of off-takers facilitating bean grain trade to pull seed demand and supply response in Eastern and Southern Africa - Rubyogo, Jean-Claude; Kalemera, Sylvia Monica; Birachi, Eliud Abucheli; Aseete, Paul (2022)
Conventional model for creating demand for seed of leguminous crops has been through promotional events such as agricultural show, field days, seed fairs, demonstrations, use of print media and mass media campaigns etc. Other emerging approaches to create demand and increase adoption of improved legume crop variety seeds include use of Multi Stakeholder Platforms (MSPs). These have proven efficient in delivering and fostering demand for seeds of leguminous crops (Lorlamen et al., 2021; Ojiewo et al., 2020; Rubyogo et al., 2019). The MSPs bring together various actors to boost their networks, and resources. As such, combining promotional activities of varieties, seed, integrated management with seed and grain trade. However, conventional methods and less targeted MSP interventions may fail to create sustained seed demand hence less seed business could limit quality seed supply to farmers and contribute to slow adoption of new varieties.